2020
DOI: 10.1038/s41467-020-15131-0
|View full text |Cite
|
Sign up to set email alerts
|

Dichloromethylation of enones by carbon nitride photocatalysis

Abstract: Small organic radicals are ubiquitous intermediates in photocatalysis and are used in organic synthesis to install functional groups and to tune electronic properties and pharmacokinetic parameters of the final molecule. Development of new methods to generate small organic radicals with added functionality can further extend the utility of photocatalysis for synthetic needs. Herein, we present a method to generate dichloromethyl radicals from chloroform using a heterogeneous potassium poly(heptazine imide) (K-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
60
2
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 111 publications
(75 citation statements)
references
References 51 publications
0
60
2
3
Order By: Relevance
“… 8 The extreme of nitrogen introduction in a graphitic structure leads to carbon nitride (CN), a mid band gap semiconductor with the ideal formula C 3 N 4 , which has attracted much attention in the past decade, especially for photocatalysis and very recently also for optical and optoelectronic applications. 9 15 …”
Section: Introductionmentioning
confidence: 99%
“… 8 The extreme of nitrogen introduction in a graphitic structure leads to carbon nitride (CN), a mid band gap semiconductor with the ideal formula C 3 N 4 , which has attracted much attention in the past decade, especially for photocatalysis and very recently also for optical and optoelectronic applications. 9 15 …”
Section: Introductionmentioning
confidence: 99%
“…Visible light‐irradiated reactions always provide efficient and convenient methods towards complex structures. In 2020, Savateev developed a method to generate dichloromethyl radicals from chloroform using a heterogeneous potassium poly(heptazine imide) (K‐PHI) photocatalyst under visible light irradiation conditions [32] . The reaction was conducted between enones and chloroform, with triethanolamine (TEOA) as electron donor and K‐PHI as the photocatalyst under irradiation of blue LED to generate a variety of γ,γ‐dichloroketones in yields up to 89% (Scheme 26).…”
Section: Di‐ and Trichloromethylation Using Polyhalomethanes As The Pmentioning
confidence: 99%
“…Very recently, Savateev and co‐workers reported that chloroform, an inactive halide, could be used to generate a dichloromethyl radical using a heterogeneous potassium poly(heptazine imide) (K‐PHI) photocatalyst ( Figure ). [ 55 ] As a result, dichloromethylation of enones was developed. In terms of the mechanism, the reaction is initiated by photoexcited electron‐induced SET reduction of chloroform to dichloromethyl radical.…”
Section: Semiconductor Photocatalytic Advanced Synthetic Transformationsmentioning
confidence: 99%
“…Dichloromethylation of enones by carbon nitride photocatalysis and flow photoreactor design used in this work. [ 55 ] Reproduced with permission. [ 55 ] Copyright 2020, Springer Nature.…”
Section: Semiconductor Photocatalytic Advanced Synthetic Transformationsmentioning
confidence: 99%